Method for detecting antioxidant in butanedisulfonic acid ademetionine for injection - HAN QIANRU; ZONG YINGYING; LUO HUIRU; WANG YAJING; MA MINGZHUO; CHEN BICHU; FAN SIYU; YANG FANG; FAN YANLONG (2025)
The invention relates to the technical field of medicine detection, and particularly discloses a method for detecting an antioxidant in butanedisulfonic acid ademetionine for injection. The method comprises the following steps: firstly, dissolving an ademetionine butanedisulfonate sample for injection in a solvent for injection for pretreatment, passing through a C18 solid-phase extraction column, and eluting with methanol, so that the antioxidant in the ademetionine butanedisulfonate sample for injection can be fully extracted, and the recovery rate is relatively high; then a C18 chromatographic column with a specific specification is adopted to carry out liquid chromatographic analysis on the test solution, and accurate detection of the antioxidant and the content of the antioxidant in the methionine butanedisulfonate for injection is realized at the same time; by limiting the conditions of the ultrahigh liquid chromatography, the peak response intensity of the test solution and the reference solution is im